Re-evaluating the gender gap: a cross-sectional analysis of accepted American Academy of Neurology annual meeting abstracts in 2020 and 2021 - Kim, Minseon; Kim, Youngran; Sharrief, Anjail Z.; Nguyen, Thy P. (Frontiers in Research Metrics and Analytics, 2024)
Background and objective Prior studies reveal that invited speaker panels, editorial boards, authors of practice guidelines, and senior authors of published articles are disproportionately male in the neurology field. We aimed to analyze a gender gap in authorship of accepted abstracts to the American Academy of Neurology annual meetings in 2020 and 2021. Design/methods This is a cross-sectional study evaluating the proportions of female first and senior abstract authors in 2020 and 2021. Abstracts were reviewed manually (n = 3,211 in 2020; n = 2,178 in 2021). Data were collected regarding the gender of first and senior authors, subspecialties, and origin of research (USA, international, or corporate-affiliated). Then, we compared the percentages of female first and senior authors in the 2 years to assess for any short-term effects of the COVID-19 pandemic. Results Accepted abstracts with female first and senior authors comprised 46%, 34% in 2020, and the same in 2021, without change. Female senior authors had a significantly higher proportion of female first authors than their male senior author counterparts. The analysis of subspecialties with more than 100 abstracts showed the lowest percentages of female senior authors was oncology (24.7%), sleep (25.5%), headache (28.7%), and cerebrovascular disease (29%) in 2020. Cerebrovascular disease (29%) and behavioral neurology (24.7%) had the lowest percentage of female senior authors in 2021. In the analysis of the origin of research, corporate-affiliated authors had the lowest percentages of female first (34 and 36%) and senior authors (22.6 and 27.6%). Conclusion The gender gap in neurology was reaffirmed in regards to female senior authorship overall and in subgroups of abstracts including cerebrovascular disease, headache, behavioral neurology, sleep, oncology, and corporate-affiliated research.